Cardiometabolic determinants of aortic and carotid intima-media thickness in adolescence - Laitinen, Tomi T.; Mikola, Hanna; Pahkala, Katja; Mykkänen, Juha; Rovio, Suvi P.; Niinikoski, Harri; Rönnemaa, Tapani; Viikari, Jorma S. A.; Jula, Antti; Lagström, Hanna; Salo, Pia; Nuotio, Joel; et al. (ELSEVIER IRELAND LTD, 2025)
Background and aims: Comprehensive longitudinal data in healthy populations on cardiometabolic determinants of arterial intima-media thickness (IMT), especially aortic IMT, in adolescence are lacking. We aimed to examine in detail how cardiometabolic risk factors associate with aortic and carotid intima-media thickness (IMT) in adolescence.
Methods: Participants (n = 522) were healthy individuals from Special Turku Coronary Risk Factor Intervention Project. IMT of the abdominal aorta and common carotid artery was measured repeatedly with ultrasonography at the age of 11, 13, 15, 17 and 19 years. Data on cardiometabolic risk markers were available beginning from early childhood.
Results: Between ages 11 and 19 years, body mass index (BMI), waist circumference, systolic and diastolic blood pressure, serum total cholesterol, non-HDL-cholesterol, and apolipoprotein B levels, insulin and insulin resistance indicated by homeostasis model of insulin resistance (HOMA-IR), C-reactive protein, and smoking associated directly with aortic IMT. For carotid IMT, a direct association was found with BMI, waist circumference, systolic blood pressure and smoking. In multivariate analyses, BMI((3 = 5.49, SE = 1.01, P <0.0001) and HOMA-IR ((3 = 16.79, SE = 7.45, P = 0.02) remained as determinants of aortic IMT. Correspondingly, BMI((3 = 1.78, SE = 0.42, P < 0.0001) and systolic blood pressure ((3 = 0.38, SE = 0.10, P = 0.0001) determined carotid IMT. Participants with longitudinal aortic or carotid IMT above/equal the 80th percentile had higher BMI measured from infancy than their peers with longitudinal IMT below the 80th percentile.
Conclusions: In adolescence, several cardiometabolic risk factors associate with aortic IMT while these links are less evident for carotid IMT. Aortic IMT may serve as a more sensitive marker than carotid IMT of early vascular remodeling.